2020
DOI: 10.3389/fgene.2020.00013
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Rice Florigen Gene RFT1 on the Amino Acid Content of Unmilled Rice

Abstract: In rice, the contents of protein and amino acids are the major parameters of nutritional quality. Co-localization of quantitative trait loci (QTLs) for heading date and protein content were reported, but pleiotropism of heading-date genes on protein contents has not been investigated. Here, we reported that rice florigen gene RFT1 plays an important role in controlling amino acid contents of rice grain. Firstly, 73 QTLs for the contents of 17 amino acids in unmilled rice were detected using recombinant inbred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The heading date is known to be associated with a range of agronomic traits affecting yield, such as plant height, panicle number, grain number, and weight, and those affecting eating and cooking quality, such as AC and PC [3,[27][28][29][30]. Therefore, to facilitate the use of different Hd1 alleles in rice molecular breeding, it is important to evaluate the pleiotropic effects of Hd1 and the effects of different Hd1 alleles on major agronomic traits.…”
Section: Discussionmentioning
confidence: 99%
“…The heading date is known to be associated with a range of agronomic traits affecting yield, such as plant height, panicle number, grain number, and weight, and those affecting eating and cooking quality, such as AC and PC [3,[27][28][29][30]. Therefore, to facilitate the use of different Hd1 alleles in rice molecular breeding, it is important to evaluate the pleiotropic effects of Hd1 and the effects of different Hd1 alleles on major agronomic traits.…”
Section: Discussionmentioning
confidence: 99%
“… Zhang et al (2020) found that the regions of several QTLs for grain weight influence HD between the two parental varieties. Xie et al (2020) also reported the pleiotropic effects of the rice florigen gene RFT1 on the amino acid content of unmilled rice. Ouyang et al (2020) indicated that OsHG3 can affect rice palea development, grain yield, and quality at the same time.…”
Section: Discussionmentioning
confidence: 98%
“…Trait selection heavily influences pleiotropy results. Small subsets of measured traits originating from the same phytomer or highly correlated traits such as amino acid content [ 60 ] or grain quality [ 61 ] may already share similar regulatory pathways leading to enrichment in pleiotropic loci [ 23 ]. This may lead to unrealistic expectations of the pervasiveness of pleiotropy genome-wide.…”
Section: Discussionmentioning
confidence: 99%